Perancangan Poster Media Sosial Kampanye Penghematan Air - Desmond Christian Mauwa; Agus Danarto (Lembaga Pengembangan Kinerja Dosen, 2026)
Clean water is a fundamental necessity with increasingly limited availability due to unwise household consumption. Although research on water crises is extensive, engaging educational visual communication media to build public awareness remains scarce. This research aims to design informative visual communication media in the form of Instagram posters as a tool for water conservation education among teenagers. The method employed is qualitative descriptive, adapting Robin Landa's